SOSIALISASI DAN IMPLEMENTASI MATA KULIAH PEMINATAN BAHASA PRANCIS DALAM MENGHADAPI TANTANGAN DUNIA KERJA PASCA PANDEMI - Rini, Setia; Rosita, Diana; Ikhtiarti, Endang; Trisna, Indah Nevira (Dimasatra, 2023)
Job  opportunities  for  graduates  of  the French  Language Studies Program (PS) are currently more and more promising. But of course, graduates must have good or even superior skills to compete with graduates of the same field from various Indonesian universities. Therefore, the existence of specialization courses (MK) is a very good  step  to  equip  graduates  with  qualified  skills,  especially  in  the  field  of  French. Specialized courts can help graduates be able to compete in a wider range of professions. Employment opportunities for graduates will be increasingly open. But in reality, there are still students, alumni and stakeholders who don't know and understand this. Thus, through this service activity, it is hoped that the various parties directly involved will be able to learn about the importance of the specialized tribunal during studies in the French Language Studies Program. Not only the provision of French with a literary and pedagogical basis, but also competence in the field of specialized French (FOS / French for Specific Objectives) to be able to compete in an increasingly difficult professional world. The challenges of the disruptive era and the 4.0 industrial revolution and the 5.0 society require students and alumni as well as stakeholders to be able to adapt quickly to the changes taking place both in the world of education than professionals.